Phase 1/2 study of a novel 24-valent pneumococcal vaccine in healthy adults aged 18 to 64 years and in older adults aged 65 to 85 years. Issue 31 (29th July 2022) - Chichili, Gurunadh R.; Smulders, Ronald; Santos, Vicki; Cywin, Beth; Kovanda, Laura; Van Sant, Charles; Malinoski, Frank; Sebastian, Shite; Siber, George; Malley, Richard
Abstract: Background: Pneumococcal diseases remain prevalent despite available polysaccharide and conjugate vaccines. This phase 1/2 study evaluated safety/tolerability and immunogenicity of a novel 24-valent pneumococcal vaccine (ASP3772) based on high-affinity complexing of proteins and polysaccharides. Methods: Pneumococcal vaccine–naïve adults aged 18–85 years were randomized to receive either ASP3772 or PCV13 (13-valent conjugate vaccine). Participants received a single intramuscular injection of ASP3772 (1-, 2-, or 5-µg dose per polysaccharide) or PCV13. A separate, nonrandomized group of PCV13-vaccinated participants (65–85 years) received PPSV23 (23-valent polysaccharide vaccine). Assessments were obtained through Day 7 for reactogenicity, through Day 30 for safety and tolerability, and through Month 6 for serious adverse events. Immunogenicity was measured at Day 30 using assays for functional opsonophagocytic activity (OPA) and pneumococcal serotype-specific anticapsular polysaccharide immunoglobulin G for each serotype. Results: In both age cohorts, the most frequently reported local reactions were self-limited tenderness and pain after ASP3772 at all dose levels or after PCV13, occurring within 2–3 days. Fatigue, headache, and myalgia were the most frequently reported systemic reactions following either vaccine. Robust OPA responses for all serotypes were observed across all ASP3772 dose groups in both age cohorts. Older adults (aged 65–85 years) who received ASP3772 had significantly higher immune responses to several PCV13 serotypes and all non-PCV13 serotypes than participants who received PCV13. OPA responses to the ASP3772 5-µg dose were significantly higher for several serotypes in naïve participants than in older adults with prior exposure to PCV13 who were administered PPSV23 in this study. Conclusions: These results demonstrate that ASP3772 is well tolerated, highly immunogenic, and in adults may offer significantly broader protection than existing pneumococcal vaccines. Clinicaltrials.gov: NCT03803202